Anatomic All-Inside Anterior Cruciate Ligament Reconstruction Using the Translateral Technique - Wilson, Adrian J. (Elsevier, 2013)
There is growing evidence that anatomic placement of the femoral tunnel in anterior cruciate ligament reconstruction confers biomechanical advantages over the traditional tunnel position. The anteromedial portal technique for anatomic anterior cruciate ligament reconstruction has many well-described technical challenges. This article describes the translateral all-inside technique, which produces anatomic femoral tunnel placement using direct measurement of the medial wall of the lateral femoral condyle and outside-in drilling. All work is carried out through the lateral portal with all viewing through the medial portal. Thus there is no need for an accessory medial portal or hyperflexion of the knee during femoral socket preparation. A single quadrupled hamstring graft is used with cortical fixation at both the femoral and tibial tunnels.